AUGMENTED REALITY IN THE PROGRAM ‘UNA HORA MENOS’ FROM RADIO TELEVISION CANARIA: the eruption of the volcano Cumbre Vieja of the Palma (Spain) - Jiménez Narros, Carlos; Herrero de la Fuente, Mercedes; Puelles Gutiérrez, Miriam (Brazilian journalism research, 2023)
ABSTRACT – The main Spanish television channels have incorporated augmented reality into their information content. Radio Televisión Canaria (RTVC), in programs such as ‘Una hora menos’, significantly includes this narrative element in the news coverage of the eruption of the Cumbre Vieja volcano in La Palma (Spain). This research focuses on its use during the period of activity of the volcano, and designs a pattern of analysis to classify the broadcasted pieces. In-depth interviews with RTVC professionals and technology experts add value to this study. The results show that static and enveloping AR elements predominated. In the former, the informative function stands out, and in the latter, their didactic nature. The anchor’s interaction was limited. Music was always present and sound effects were frequent. RTVC has won numerous awards for the best news coverage in 2021. RESUMO – Os principais canais de televisão espanhóis incorporaram a realidade aumentada em seu conteúdo de assuntos atuais. A Radio Televisión Canaria (RTVC), em programas como ‘Una hora menos’, inclui este elemento narrativo de forma significativa na cobertura jornalística da erupção do vulcão Cumbre Vieja em La Palma (Espanha). Esta pesquisa se concentra em seu uso durante o período de atividade vulcânica e projeta um padrão de análise que estabelece uma classificação das peças transmitidas. Entrevistas em profundidade com profissionais e especialistas em tecnologia da RTVC agregam valor a este estudo. Os resultados mostram que predominam as peças estáticas e imersivas. Na primeira, destaca-se a função informativa e, na segunda, sua natureza didática. A interação do apresentador é limitada. A música está sempre presente e os efeitos sonoros são freqüentes. RTVC ganhou inúmeros prêmios para a melhor cobertura jornalística em 2021. RESUMEN – Las principales televisiones españolas han incorporado la realidad aumentada a sus contenidos de actualidad. Radio Televisión Canaria (RTVC), en programas como ‘Una hora menos’, incluye este elemento narrativo de manera significativa en la cobertura informativa de la erupción del volcán Cumbre Vieja en La Palma (España). Esta investigación se centra en su empleo durante el periodo de actividad del volcán y diseña un patrón de análisis que establece una clasificación de las piezas emitidas. Las entrevistas en profundidad a profesionales de la RTVC y a expertos en tecnología aportan un valor añadido a este estudio. Los resultados muestran que predominan las piezas estáticas y las envolventes. En las primeras destaca la función informativa y en las segundas su carácter didáctico. La interacción del presentador es limitada. La música está siempre presente y los efectos sonoros son frecuentes. La RTVC ha obtenido numerosos galardones a la mejor cobertura informativa en 2021.